Endoscopic sphincteroplasty: a novel and safe alternative to papillotomy in the management of bile duct stones. Issue 1 (January 1994) - Mac Mathuna, P; White, P; Clarke, E; Lennon, J; Crowe, J
Abstract : Removal of bile duct stones during endoscopic retrograde cholangiopancreatography (ERCP) usually includes papillotomy. Papillotomy is associated with occasional complications and in addition, the longterm sequelae of papillotomy in young patients having laparoscopic cholecystectomy remain unclear. As an alternative to papillotomy, this study prospectively evaluated the efficacy and safety of endoscopic balloon sphincteroplasty to facilitate bile duct clearance. Of 32 patients with bile duct stones (diameter 3-30 mm) at ERCP, sphincteroplasty was considered inappropriate in four patients because of stone size (> 20 mm) necessitating papillotomy for bile duct clearance. Sphincteroplasty was performed in the remaining 28 patients to permit duct clearance by dormier basket, balloon or mechanical lithotripsy. The bile duct was cleared in 22 patients (79%) while additional measures including papillotomy or stent insertion were required in the remaining six patients (21%) because of stone size or technical difficulties. There was no associated papillary haemorrhage. Pancreatitis was seen in one patient (4%) but resolved within 24 hours. Our preliminary experience suggests that sphincteroplasty is a safe and effective sphincter preservation technique that significantly reduces the necessity for papillotomy in the management of bile duct stones.